Heather George interviewed by Hazel de Berg in the Hazel de Berg collection - George, Heather; De Berg, Hazel, 1913-1984. (1965)
George speaks about her art studies ; her work in photography ; her painting method and mediums used.
Digital master available
Transcript available (3 p.)
Keywords: George, Heather -- Interviews; Women painters -- Australia -- Interviews; Women photographers -- Australia -- Interviews